Kualitas Embrio pada Sapi Simmental dan Limousin dengan Kadar Protein Pakan Berbeda - Hardiyanto, D.; Sumantri, C.; Zamanti, D. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2016)
Enhancement beef population could be conducted using the MOET (multiple ovulation, the embryo transfer). This method is done to ensure the quality of embryos have high production. Determination of embryo quality on this method gave fed with 15%-20% protein levels. This research was aim to evaluate influenced of different gave fed againt different breed. The evaluation was done by observing at the influence of the environment against the production of embryos. The assessment was conducted using factorial design experiment. The evaluation results showed average production of embryos in different breeds was not significant (P>0.05) influence to embryo quality quality. An important factor for obtaining the production of viable embryo transfer were not  linked to individual breeds